Protection of the plasma facing components in the WEST tokamak, progress and development in view of ITER - M. Houry; M-H. Aumeunier; Y. Corre; X. Courtois; R. Mitteau; TH. Loarer; L. Dubus; E. Gauthier; J. Gerardin; V. Gorse; E. Grelier; A. Juven; et al. (Nuclear Fusion)
The protection of the inner walls of magnetic confinement fusion research reactors is a crucial issue, particularly in this research context where plasma scenarios are explored to reach high power performance, thus leading to high temperature of the plasma facing components (PFCs), possibly close to their technological limitation. The aim is to protect the PFCs from damage during experimental campaigns, whilst enabling the expansion of the operational domain toward long duration and high power performances. With nearly 35 years of operation of Tore Supra and now WEST, CEA’s magnetic fusion research institute, the IRFM, has deployed a system combining thermal instrumentation, modeling of the heat transfer and photonic emission, signal processing and understanding of the physics of plasma-wall interaction to provide an optimized and controlled protection of the PFCs in metallic environment (with tungsten, bore, copper and stainless steel materials). In this context, the WEST Tokamak is a relevant Fusion facility capable of combining steady-state (Vloop ∼ 0) 1000 s long pulse operation with up to 6 MW m ^−2 on its divertor together with an advanced first wall protection system that could be deployed on ITER and future Fusion machines. The paper describes the wall protection system installed on WEST, highlighting its particular features and recent results.